Comparison of Carbapenem vs. Amikacin Antimicrobial Therapy for Pediatric Acute Pyelonephritis Caused by Extended-Spectrum Β-Lactamase-Positive Enterobacteriaceae - Burcu Ceylan Cura Yayla; Tuğba Bedir Demirdağ; Anıl Tapısız; Yeşim Özdemir Atikel; Hasan Tezer; Elif Ayça Şahin; Kayhan Çağlar; Sevcan A. Bakkaloğlu; Necla Buyan (Children, 2025)
Objectives: Acute pyelonephritis (APN) caused by extended-spectrum β-lactamase (ESBL)-positive Enterobacteriaceae poses a growing therapeutic challenge in children, as carbapenems remain the mainstay of treatment even when susceptibility to alternative agents such as amikacin is demonstrated. However, the widespread and inappropriate use of carbapenems can lead to carbapenem resistance. The aim of this study was to compare the clinical efficacy of amikacin and carbapenems in the management of pediatric acute pyelonephritis caused by ESBL-positive Enterobacteriaceae. Methods: We analyzed cases of pediatric acute pyelonephritis caused by ESBL-positive Enterobacteriaceae that were treated with either carbapenems or amikacin over a two-year period. This study compared microbiological cure, clinical improvement, and recurrence rates across the amikacin and carbapenem treatment groups. Results: Fifty-five patients were evaluated. The median age of the patients was 3 years (range, 0.1–13 years). The causative agents were E. coli in 43 cases (78.2%) and Klebsiella spp. in 12 cases (21.8%). All were susceptible to both carbapenem and amikacin in vitro. Twenty patients (36.3%) received a carbapenem and thirty-five (63.7%) received amikacin. Twenty-four (43.6%) had an underlying urological disease. No difference was observed between the groups in terms of microbiological cure, clinical improvement, or recurrence rates. Conclusions: Amikacin may be a potential alternative to carbapenems for treating pediatric ESBL-positive APN when in vitro susceptibility is confirmed.